Do Museums Change Lives?: Ninth Stephen Weil Memorial Lecture. (April 2016) - Fleming, David
Abstract: No museum is actually "neutral, " ever. This article presents the keynote address presented at the annual conference of the International Committee on Museum Management (INTERCOM) and of the Federation of International Human Rights Museums (FIHRM). In it, the author lays out the provocative case that museums not only are not, but should not be "neutral" when it comes to issues of human rights and social justice. Museums need not present both sides of every argument, or retain a lofty academic tone when it comes to the injustices of the present and the past. As an alternative course, the author presents a framework published by the British Museums Association, entitled Museums Change Lives, which offers a vision for museums to engage with challenging topics. He then offers a series of examples where Museums have embraced a new role as a promoter of social good.